Social Business in the Context of Sustainable Development - Neiva, Samara da Silva; MacQueen, Jameson Henry; de Andrade Guerra, José Baltazar Osório Salgueirinho (Decent Work and Economic Growth, 2021)
Social business is a new kind of business model, which integrates multiple dimensions and meanings, including management experiences from private, public, and nonprofit organizations. Social business has a goal of solving social problems through entrepreneurship, combining efficiency, innovation, and resources from a traditional enterprise with mission and values of a nonprofit organization
Keywords: Ouvrages de référence; Relations industrielles; Réservé UdeM